1981
DOI: 10.1099/00222615-14-2-195
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ethyleneglycoltetra-acetic acid on bactericidal activity of human serum against Escherichia coli

Abstract: SUMMARY.The effects of ethyleneglycoltetra-acetic acid (EGTA) and EGTA+magnesium (MgEGTA) on the viable counts of 10 strains of Escherichia coli 0 6 have been studied in normal human serum (NHS), heat-inactivated serum (HIS) and in culture media with and without the addition of a fl-lactam antibiotic. The addition of EGTA to NHS largely prevented bactericidal activity against serum-sensitive strains while, in contrast, it reduced the growth of a serum-resistant strain. These apparently paradoxical effects are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our previous study of the effect of MgEGTA on the bactericidal activity of human serum (Roberts and Phillips, 1981) we found that promptly serum-sensitive strains of E. coli serogroup 0 6 were killed rapidly by the classical pathway and that, when this pathway was eliminated by the chelator, delayed killing occurred by the alternative pathway; this was comparable with the findings of Traub and Kleber (1976) for strains of Serratia marcescens. In the present study of other 0-serogroups common amongst urinary isolates of E. coli, most strains again responded in a similar way but further patterns of response to serum have emerged; the 0 1 isolate, no.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In our previous study of the effect of MgEGTA on the bactericidal activity of human serum (Roberts and Phillips, 1981) we found that promptly serum-sensitive strains of E. coli serogroup 0 6 were killed rapidly by the classical pathway and that, when this pathway was eliminated by the chelator, delayed killing occurred by the alternative pathway; this was comparable with the findings of Traub and Kleber (1976) for strains of Serratia marcescens. In the present study of other 0-serogroups common amongst urinary isolates of E. coli, most strains again responded in a similar way but further patterns of response to serum have emerged; the 0 1 isolate, no.…”
Section: Discussionsupporting
confidence: 77%
“…These differences could be a reflection of nutritional requirements or of the effectiveness of a non-complement-dependent bacteriostatic mechanism (Traub and Kleber, 1976). The generally reduced growth when MgEGTA is added to HIS has been noted before for E. coli 0 6 strains (Roberts and Phillips, 1981) and probably indicates that MgEGTA chelates other divalent cations important for growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extremely labile nature of nascent C3b (half‐life of approximately 60 μs 48 ) and low activation rates because of the bias toward inhibition of the pathway by FH and FI makes the “tickover” mechanism alone highly unlikely to effectively surveil pathogens. Therefore, it is no surprise that killing of most pathogens is either abrogated or considerably delayed when only the AP is active 49–58 …”
Section: Activation Of the Alternative Pathway On Microbesmentioning
confidence: 99%